Anti-biofilm activity of dalbavancin against methicillin-resistant Staphylococcus aureus (MRSA) isolated from human bone infection. (3rd October 2021) - Silva, Vanessa; Miranda, Carla; Bezerra, Mário; Antão, H. Sofia; Guimarães, João; Prada, Justina; Pires, Isabel; Maltez, Luís; Pereira, José E.; Capelo, José L.; Igrejas, Gilberto; Poeta, Patrícia
Abstract : The presence of methicillin-resistant Staphylococcus aureus (MRSA) in bone infections difficults its treatment and is a sign of concern. The aim of this study was to evaluate in vitro activity of dalbavancin on pre-established adhered cells and 24 h old biofilms of MRSA strains isolated from a human bone infection. Thirty-three MRSA were isolated from osteomyelitis episodes. The antimicrobial susceptibility of these strains was assessed by the Kirby-Bauer disc diffusion method and the presence of resistance genes was screened by PCR. MRSA planktonic minimum inhibitory concentration and minimum bactericidal concentration were assessed. Minimum biofilm eradication concentration (MBEC) was performed by the microtiter biofilm formation assay. All 33 MRSA strains were classified as multidrug-resistant strains and susceptible to dalbavancin. Dalbavancin inhibited the growth of 54.6% and 52% of strains at the concentrations of 0.05 µg/mL and 1 µg/mL, respectively. The MBEC values up to 0.4 µg/mL demonstrated that dalbavancin was active against most strains in pre-established adhered cells and 24 h old biofilms. The current results show that dalbavancin is active against adhered cells and biofilms in vitro, suggesting that this antimicrobial agent may be an option for the treatment of bone infections caused by MRSA.